Odpowiedź :
Odpowiedź:
a) (-5) +12 (-6) = 12 + (-11) = 1
b) (-8) + (-4) + 6 = (-12) +6 = -6
c) 20 + (-9) + (-10) = 20 + (-19) = 1
d) (-7) + (-9) + 16 = (-16) + 16 = 0
e) 27 + (-12) + (-15) = 27 + (-27) = 0
f) (-20) + 17 + (-3) = 17 + (-23) = -6
pozdrawiam
Odpowiedź:
zad 3
a) (-5) + 12 + (-6) = 12 + (-11) = 1
b) (-8) + (-4) + 6 = 6 + (-12) = -6
c) 20 + (-9) + (-10) = 20 + (-19) = 1
d) (-7) + (-9) + 16 = 16 + (-16) = 0
e) 27 + (-12) + (-15) = 27 + (-27) = 0
f) (-20) + 17 + (-3) = 17 + (-23) = -6
Szczegółowe wyjaśnienie: